Financial technology: The catalyst for BRICS' economic and financial leap - M, Dhaya; N, Sundaram (The Economics and Finance Letters, 2025)
This research attempts to ascertain how fintech contributes to the financial development and economic expansion of the BRICS nations. Samples were gathered between 2002 and 2021 using panel data analysis with fixed effects as the research approach. OLS regression was used for analysis. Variables are collected from World Development Indicators and data analysis is done using Gretl software. Three hypotheses are put out in the study and are validated based on the data collected. As per the first hypothesis, fintech is having a beneficial impact on the GDP which is used as a gauge for the nation's economic growth. A second hypothesis posits that fintech impacts the overall money supply which serves as a gauge for financial progress. The third hypothesis states that fintech impacts bank deposits relative to GDP; the second metric chosen to measure financial development is not favorable according to the results. The impact of fintech on financial development and economic growth shows positive impacts. Fintech can enhance the overall economic growth of emerging economies. Maximum utilization of upcoming technology can result in financial development. Emerging economies can benefit from the use of financial technologies to further their financial and economic development. The analysis highlights how crucial technology is to the financial industry.